Kirigami‐Inspired Pressure Sensors for Wearable Dynamic Cardiovascular Monitoring. Issue 36 (20th July 2022) - Meng, Keyu; Xiao, Xiao; Liu, Zixiao; Shen, Sophia; Tat, Trinny; Wang, Zihan; Lu, Chengyue; Ding, Wenbo; He, Ximin; Yang, Jun; Chen, Jun
Abstract: Continuously and accurately monitoring pulse‐wave signals is critical to prevent and diagnose cardiovascular diseases. However, existing wearable pulse sensors are vulnerable to motion artifacts due to the lack of proper adhesion and conformal interface with human skin during body movement. Here, a highly sensitive and conformal pressure sensor inspired by the kirigami structure is developed to measure the human pulse wave on different body artery sites under various prestressing pressure conditions and even with body movement. COMSOL multiphysical field coupling simulation and experimental testing are used to verify the unique advantages of the kirigami structure. The device shows a superior sensitivity (35.2 mV Pa −1 ) and remarkable stability (>84 000 cycles). Toward practical applications, a wireless cardiovascular monitoring system is developed for wirelessly transmitting the pulse signals to a mobile phone in real‐time, which successfully distinguished the pulse waveforms from different participants. The pulse waveforms measured by the kirigami inspired pressure sensor are as accurate as those provided by the commercial medical device. Given the compelling features, the sensor provides an ascendant way for wearable electronics to overcome motion artifacts when monitoring pulse signals, thus representing a solid advancement toward personalized healthcare in the era of the Internet of Things. Abstract : A kirigami‐inspired pressure sensor is developed for wearable dynamic cardiovascular monitoring. Utilizing the vertical kirigami‐inspired structure and a simple fabrication process, the sensor provides an ascendant way for wearable bioelectronics to overcome motion artifacts when monitoring human pulse signals, thus representing a solid advancement toward personalized cardiovascular monitoring in the era of the Internet of things.